A Novel BoHV-1-Vectored Subunit RVFV Vaccine Induces a Robust Humoral and Cell-Mediated Immune Response Against Rift Valley Fever in Sheep - Selvaraj Pavulraj; Rhett W. Stout; Shafiqul I. Chowdhury (Viruses)
Rift Valley fever (RVF) is a vector-borne zoonotic viral disease that causes abortion storms, fetal malformations, and neonatal mortality in livestock ruminants. In humans, RVF can lead to hemorrhagic fever, encephalitis, retinitis, or blindness, and about 1% of patients die. Since there are no registered vaccines for human use, developing RVF vaccines for use in animals is crucial to protect animals and prevent the spread of the virus from infecting humans. We recently developed a live bovine herpesvirus type 1 quadruple gene-mutant vector (BoHV-1qmv) that lacks virulence and immunosuppressive properties. Further, we engineered a BoHV-1qmv-vectored subunit Rift Valley fever virus (RVFV) vaccine (BoHV-1qmv Sub-RVFV) for cattle, in which a chimeric polyprotein coding for the RVFV Gc, Gn, and bovine granulocyte–macrophage colony-stimulating factor (GMCSF) proteins is fused but cleaved proteolytically in infected cells into individual membrane-anchored Gc and secreted Gn-GMCSF proteins. Calves vaccinated with the BoHV-1qmv Sub-RVFV vaccine generated moderate levels of RVFV-specific serum-neutralizing (SN) antibodies and cellular immune responses. In the current study, we repurposed the BoHV-1qmv Sub-RVFV for sheep by replacing the RVFV Gc and Gn ORF sequences codon-optimized for bovines with the corresponding ovine-codon-optimized sequences and by fusing the sheep GM-CSF ORF sequences with the Gn ORF sequence. A combined primary intranasal-plus-subcutaneous primary immunization induced a moderate level of BoHV-1 (vector)- and vaccine strain MP12-specific SN antibodies and MP-12-specific cellular immune responses. Notably, an intranasal booster vaccination after 29 days triggered a rapid (within 7 days) rise in MP-12-specific SN antibody titers. Therefore, the BoHV-1qmv-vectored subunit RVFV vaccine is safe and highly immunogenic in sheep and can potentially be an efficient subunit vaccine for sheep against RVFV.